Evaluation of the prevalence of angiotensin-converting enzyme and angiotensinogen polymorphic genes in primary hypertensive patients in the Peruvian population - Lizaraso S., Frank (2022)
Evaluation of the Prevalence on the Polymorphic genes from the Angiotensin Converting Enzyme and from angiotensinogen on Primary Hypertense People on Peruvian Population.We have decided to identify the prevalence in our population about the most important genetic polymorphisms in the cardiovascular diseases such as the I/D polymorphism of the gene at the angiotensin converting enzyme (ACE) and the polymorphism of the gene at the angiotensinogen (AGT), and also his association with primary High Blood Pressure (HBP). This study has also tried to show that the DD genotype of ACE gene is associated with greater levels of serum ACE at HBP.This study of the type: Case - Control, National Multicentric has included 238 patients, males and females, being 118 hypertensives, who come from 48 families that are compared with 120 normotensives.Some samples have been extracted for the DNA, it has been made the polymorphism analysis for the PCR at the ACE and AGT genes, dosage of serum ACE and the biochemical determination of the lipidic profile.Results: The DD prevalence was of (13/118) 11% and the TT prevalence was (78/118) 66%. We have obtained significant differences on the values of serum ACE: DD 44 ± 20 U/1, ID 33 ± 19 UIL, 13 ± 9.8 U/1 (p<0,001), it has not been association from HBP with those genotypes.Conclusion: We must say that in our sample group the prevalence of TT genotype is bigger than the prevalence of DD genotype. There is a higher level of serum ACE at the DD genotype carriers. We haven't fount any association of those genotypes with the primary HBP.